2021
DOI: 10.3389/fonc.2021.700062
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Hypoxia-Related Molecular Classification and Hypoxic Tumor Microenvironment Signature for Predicting the Prognosis of Patients with Triple-Negative Breast Cancer

Abstract: PurposeThe hypoxic tumor microenvironment was reported to be involved in different tumorigenesis mechanisms of triple-negative breast cancer (TNBC), such as invasion, immune evasion, chemoresistance, and metastasis. However, a systematic analysis of the prognostic prediction models based on multiple hypoxia-related genes (HRGs) has not been established in TNBC before in the literature. We aimed to develop and verify a hypoxia gene signature for prognostic prediction in TNBC patients.MethodsThe RNA sequencing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…p -value <0.05 were set as the thresholds ( 23 ). Meanwhile, 1,694 genes identified in previous literature were used as HRGs from the Molecular Signatures Database (MsigDB) ( 24 ). Specific hypoxia-related genes in OC were screened by the overlap of the HRGs and the DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…p -value <0.05 were set as the thresholds ( 23 ). Meanwhile, 1,694 genes identified in previous literature were used as HRGs from the Molecular Signatures Database (MsigDB) ( 24 ). Specific hypoxia-related genes in OC were screened by the overlap of the HRGs and the DEGs.…”
Section: Methodsmentioning
confidence: 99%
“…Simultaneously, lactate metabolism was related to the outcomes and immune microenvironment in skin cutaneous melanoma, kidney renal clear cell carcinoma, and BC (37)(38)(39). In BC, prognostic models have been developed solely using lactate metabolism-related genes (LMRGs) or hypoxia-related genes [HRGs] (39)(40)(41). However, considering the heterogeneity of BC and the complex interactions between hypoxia and lactate metabolism, these alone cannot fully identify the relevant characteristics of BC.…”
Section: Introductionmentioning
confidence: 99%
“…Positive HIF-1α IHC expression significantly correlated with greater tumor size, higher histological grade, positive lymph node status, and higher tumor TNM stage as well as poorer postoperative survival [ 66 ]. The enrichment of a hypoxia-related three-gene signature model was shown to predict poorer overall survival (OS) in TNBC patients [ 67 ]. Furthermore, a high combined hypoxia and immune-base gene signature score predicted a poorer prognosis among TNBC patients [ 68 ].…”
Section: Double Trouble: Hypoxia In Triple-negative Breast Cancermentioning
confidence: 99%
“…Thus, targeting hypoxia along with AR in AR-enriched TNBCs may also circumvent AR-targeted therapy resistance. Furthermore, Wnt/β-catenin signaling has been reported to be one of the most significantly deregulated pathways in CRPC and is considered a compensatory pathway that PCs activate in response to ADT [ 67 , 78 , 79 , 80 , 81 ]. Lee and colleagues showed that AR growth-driven PCs are likely low in Wnt/β-catenin signaling due to the increased affinity of β-catenin for AR rather than TCF4, as the suppression of AR activity via androgen deprivation in PC cells increased β-catenin/TCF4 target gene transcription [ 82 ].…”
Section: How Hypoxia May Be Culpable In Resistance To Androgen/ar-tar...mentioning
confidence: 99%